Microglia express distinct M1 and M2 phenotypic markers in the postnatal and adult CNS in male and female mice - Crain, Jessica M. (2013)
Although microglial activation is associated with all CNS disorders, many of which are sexually dimorphic or age-dependent, little is known about whether microglial basal gene expression is altered with age in the healthy CNS or if it is sex-dependent. Analysis of microglia from the brains of 3 day (P3) - to 12 month-old male and female C57Bl/6 mice revealed distinct gene expression profiles during postnatal development that differ significantly from adulthood. Microglia at P3 are characterized by relatively high iNOS, TNFα and arginase-1 mRNA levels, whereas P21 microglia have increased expression of CD11b, TLR4 and FcRγI. Adult microglia (2-4 months) are characterized by low pro-inflammatory cytokine expression that increases by 12 months of age. Age-dependent differences in microglial gene expression suggest that microglia likely undergo phenotypic changes during ontogenesis, although in the healthy brain they did not exclusively express either M1 or M2 phenotypic markers at any time. Interestingly, microglia were sexually dimorphic only at P3 when females had higher expression of inflammatory cytokines than males, although there were no sex differences in estrogen receptor expression at this or any other time evaluated here. Compared to microglia in vivo, primary microglia prepared from P3 mice had considerably altered gene expression with higher levels of TNFα, CD11b, arginase-1 and VEGF suggesting that culturing may significantly alter microglial properties. In conclusion, age- and sex-specific variances in basal gene expression may enable differential microglial responses to the same stimulus at different ages, perhaps contributing to altered CNS vulnerabilities and/or disease courses.